2010
DOI: 10.4041/kjod.2010.40.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance screw supported maxillary molar distalization in a parallel manner

Abstract: Objective: Intraoral noncompliance upper molar distalization techniques have gained in popularity and have subsequently found to be successful in Class II correction. The aim of the present study was to introduce a screw supported intraoral distalization appliance and investigate its efficiency. Methods: Twenty-one subjects (11 females, 10 males; average age of 14.9 years) with Angle Class II malocclusion participated in this study. Two screws were inserted behind the incisive foramen and immediately loaded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 21 publications
(41 reference statements)
2
23
0
4
Order By: Relevance
“…Fakat literatürde birinci molarların distalizasyonu sırasında maksiller üçüncü molar dişlerin pozisyonu ve angulasyonu ile ilişkili araştırma bulunmamaktadır. Araştırıcıların çoğu (12)(13)(14), distalizasyon öncesinde üçüncü molar dişleri çekmişlerdir ve distalizasyon öncesinde üçüncü molar dişlerin çekimini genellikle önermişlerdir. Bu nedenle distalizasyon mekaniklerinin maksiller üçüncü molar dişleri üzerindeki etkilerini inceleyen az çalışma mevcuttur (15)(16)(17).…”
Section: G‹ R‹fiunclassified
See 1 more Smart Citation
“…Fakat literatürde birinci molarların distalizasyonu sırasında maksiller üçüncü molar dişlerin pozisyonu ve angulasyonu ile ilişkili araştırma bulunmamaktadır. Araştırıcıların çoğu (12)(13)(14), distalizasyon öncesinde üçüncü molar dişleri çekmişlerdir ve distalizasyon öncesinde üçüncü molar dişlerin çekimini genellikle önermişlerdir. Bu nedenle distalizasyon mekaniklerinin maksiller üçüncü molar dişleri üzerindeki etkilerini inceleyen az çalışma mevcuttur (15)(16)(17).…”
Section: G‹ R‹fiunclassified
“…However, the position and angulation of the maxillary third molars when distalizing the first molars was not investigated in the literature. Most of the authors (12)(13)(14) have the maxillary third molars extracted prior to the distalization and the extraction of the third molars before distalization is usually recommended (12)(13)(14). Thus few studies (15)(16)(17) Maksiller birinci molarların bilateral distalizasyonu için çalışmada kullanılan aparey, zigomatik ankraj plakları ile kombine edilen ağız içi bir distalizasyon mekaniğidir.…”
Section: Introductionmentioning
confidence: 99%
“…To correct a molar relationship or crowding, molar distalization is frequently performed with various appliances. 10 , 11 To assess the efficacy of these appliances, superimpositions of serial cephalometric radiographs, study model photographs, and photocopies have been used in previous studies. 10 , 12 To our knowledge, there is no study that compares the superimposition of 3D digital models with cephalometric radiography and model photocopy methods in cases of molar distalization.…”
Section: Introductionmentioning
confidence: 99%
“…Using this device, bodily distalization of the molars can be achieved by applying the force at the level of its center of resistance. The distal tipping of the molars with this appliance has been reported to be 149 degrees in a previous study, while with other mini-implant-supported distalization mechanics, it has been reported to be 3 to 11.3 degrees (19,20). TSADRME, MISME, Implant-Supported RME, and Hybrid Hyrax: These appliances are various types of the Hyrax (Hyrax®; Dentaurum; Ispringen, Germany) type maxillary palatal expander.…”
Section: Noncompliance Screw-supported Maxillary Molar Distalization mentioning
confidence: 99%
“…They are as follows: Beneslider (13,14), Miniscrew-supported EZ slider (15), Implant-supported Distal Jet (16), Mini-Implant-Borne Pendulum B Appliance (17,18), Noncompliance-supported Maxillary Molar Distalization Appliance (19,20), Temporary Skeletal Anchorage Device-Supported RME (TSADRME) (21,22), Mini-Implant-Supported Maxillary Expansion (MISME) (23), Implant-Supported RME (23)(24)(25)(26), Hybrid Hyrax (27)(28)(29)(30), Frog Appliance (31), Palatally Anchored Mesialslider (29,30), Mousetrap Appliance (31), Lever Arm, and Mini-implant System (32,33).…”
Section: Introductionmentioning
confidence: 99%